Flower Development and Its Implication for Seed Production on Amorphophallus muelleri Blume (Araceae) - Santosa, Edi; Lontoh, Adolf Pieter; Kurniawati, Ani; Sari, Maryarti; Sugiyama, Nobuo (Jurnal Hortikultura Indonesia, 2016)
ABSTRACT There are many studies on agronomic and economic advantages of iles-iles (Amorphophallus muelleri Blume), leading to high demand on seed to support the rapid production expansion in many Asian countries. By contrast, there are few studies on flowering phenology and flower morphology although they affect the seed production. Therefore, we evaluated flowering phenology and flower morphology of 80 plants of A. muelleri grown in a field under 65% artificial shading net at Leuwikopo Experimental Farm IPB Darmaga, Bogor, Indonesia from May 2015 to July 2016 in order to improve seed production. A. muelleri produced solitary spadix, with female flowers at the lower part and male flowers at the upper part. Spadix grew slowly for 56-71 days after bud break, and then grew rapidly thereafter for 30-35 days until anthesis. Seed was harvested 9.6 to 10.2 months after anthesis. We devided the development of spadix into seven phases, bud break as stage I and berry maturity as stage VII. Stage VI to VII determined seed production. Seed production was also affected by roots formation and spadix size. There were strong positive correlations between lengths of the female zones with berry production. Some morphological characteristics of spadix were dependent on corm size, thus, it was likely that agronomic improvement to enhance female flower and corm sizes wasimportant in seed production. Keywords: developmental stage, female flower, iles-iles, male flower, seed production ABSTRAK Telah banyak kajian keunggulan agronomi dan ekonomi iles-iles (Amorphophallus muelleri Blume), sehingga mendorong peningkatan permintaan benih untuk mendukung perluasan areal produksi di banyak negara Asia. Namun demikian, kajian fenologi dan morfologi bunga khususnya terkait produksi benih masih terbatas. Oleh karena itu, kami mengkaji perkembangan dan morfologi 80 bunga iles-iles yang ditanam di bawah paranet 65% di Kebun Percobaan Leuwikopo IPB, Bogor, Indonesia dari Mei 2015 sampai Juli 2016 dalam rangka perbaikan produksi benih. Iles-iles menghasilkan sebuah tongkol bunga dengan bunga betina pada bagian bawah dan bunga jantan pada bagian atas. Tongkol bunga tumbuh lambat 58-71 hari setelah pecah tunas, diikuti tumbuh cepat 30-35 hari hingga antesis, dan biji dipanen 9.6 sampai 10.2 bulan setelahnya. Perkembangan bunga dari pecah tunas hingga buah matang dapat dibagi menjadi tujuh tahap. Tahap VI ke tahap VII menentukan keberhasilan produksi biji iles-iles. Selain itu, keberhasilan produksi biji juga dipengaruhi oleh keberadaan akar dan ukuran tongkol khususnya panjang bagian bunga betina. Beberapa karakter morfologi bunga iles-iles dipengaruhi oleh ukuran umbi saat tanam. Oleh karena itu, perlu perbaikan agronomis untuk meningkatkan ukuran umbi dan ukuran bunga betina guna mendukung produksi benih. Kata kunci: bunga betina, bunga jantan, iles-iles, produksi benih, tahap pertumbuhan